PENGARUH MEMPELAJARI BAHASA ASING TERHADAP PERKEMBANGAN OTAK ANAK - FURQANUL HAKIM; SARASWATI HAYLIAN CHIANI (GANEC SWARA, 2019)
Children's intelligence shows how we stimulate their brains. At present, all parents are actively looking for the best stimulus for their children's brain growth. But most parents still use traditional methods in stimulating the brains of their children. For example, parents usually use the instant method by giving their children some brain enhancing drugs. Some experts believe that this method is not an effective method to be used.   This study aims to determine the correlation of learning foreign languages with the growth of children's brains, and to find out the benefits of learning foreign languages for the growth of children's brains   This research is conducted at a course called 24 English College Bima NTB, with direct observation methods and conducted interviews based on questionnaires to respondents who are determined by techinique random sampling, then the results of the study are analyzed qualitatively and supported by references (books, printed media or electronically related to the problem).  The results of the study show that: (1). By learning foreign languages such as English, Spanish, French, etc. Can stimulate children's brain growth effectively, and intelligence on children also depends on what type of stimulus they get. (2). The benefits of mastering a foreign language are (a) it maximizes children's brain performance, (b) Children with good foreign language skills have high intelligence and creativity, (c) can decrease senile dimensions, (d). have better cognitive flexibility, (e). delay Alzheimer's disease, (f). Children are able to solve problems if they use a foreign language, (g). Good decision makers. People who think in other languages tend to make rational decisions